Study of lepton pair production by photon-photon fusion with tagged protons with the CMS experiment - Pereira, Miguel Alves Gallo (2020)
At the Large Hadron Collider (LHC), located at CERN (Geneva-Switzerland), proton beams collide at a center-of-mass energy of 13 TeV. There are four collision points where large experiments were built to study the products of these collisions. In this dissertation, we are going to focus only on the CMS (Compact Muon Solenoid) experiment. The PPS (Precision Proton Spectrometer) sub-detector system consists of a silicon tracking system to measure the position and direction of protons scattered at small angles, and a set of timing counters to measure their time of flight with high precision. One of the purposes of the PPS detector is to study central exclusive and semi-exclusive production in proton-proton collisions with high levels of pileup. These processes are characterized by the reaction p+p → p⁽*⁾ ⊕ X ⊕p⁽*⁾, where ⊕ represents rapidity gaps, X is the high-mass central system and p⁽*⁾ the final state protons, which may dissociate into a low-mass state (p*), for the semi-exclusive case. A study of the production of muon pair via photon fusion process using CMS data collected during 2017 is presented in this dissertation, with the purpose of reproducing the analysis of the article (CMS AND TOTEM COLLABORATIONS, 2018) with updated data and detector, studying and using the PPS detector information as the main tool to discriminate signal and background events and prepare the methodology that will be used in future analyses of measurements of high-mass states and searches for anomalous couplings and new physics.